The Perceived Destination Identity of Stakeholders: a Case of Chang Island - Preechawong, Panita; Sawagvudcharee, Ousanee (Journal of Education and Vocational Research, 2016)
The tourism industry in Thailand is a significant economic activity due to the large and increasing number of tourists, facilities, accommodation and revenue. It is likely to increase its contribution to the GDP from its already significant role of more than 10%. Additionally, the tourism industry career opportunities and helps spread prosperity throughout the kingdom. Chang Island is no exception. Tourism on Chang Island is arguably the most important revenue-generating sector because of the income and job creation. Much of the competition in tourism focuses on tourists’ ability to recognize and remember a particular destination as being unique. Because of this, the development and use of a strong destination identity is critical when making strategic marketing plans. Many tourists will select their holiday destination from their memory of, or recognition of a destination identity. That is why the message behind a destination identity should be a topic to highlight. The aim of this study is to gain insight into the real-life perception of Chang Island’s destination identity by its sender stakeholders. This will help the researcher identify key issues that allow for the development of a suitable guideline for review and possible revision of the island’s destination identity. A qualitative analysis of data collected in this study provides a grounded theory, to support the perception of the sender side of Chang Island’s stakeholders.